2015
DOI: 10.1080/10937404.2015.1009961
|View full text |Cite
|
Sign up to set email alerts
|

Exposures and Health Outcomes in Relation to Bioaerosol Emissions From Composting Facilities: A Systematic Review of Occupational and Community Studies

Abstract: The number of composting sites in Europe is rapidly increasing, due to efforts to reduce the fraction of waste destined for landfill, but evidence on possible health impacts is limited. This article systematically reviews studies related to bioaerosol exposures within and near composting facilities and associated health effects in both community and occupational health settings. Six electronic databases and bibliographies from January 1960 to July 2014 were searched for studies reporting on health outcomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 65 publications
(65 reference statements)
4
109
0
1
Order By: Relevance
“…There are few other studies of health effects in communities living near a composting site (Aatamila et al 2005;Browne et al 2001;Herr et al 2003a;2003b;Kramer et al1989;, and these provide limited evidence of increased exposure levels to bioaerosols at distances greater than 200m to 300m downwind of a composting site (Pearson et al 2015). Three questionnaire-based community health studies reported increases in respiratory symptoms in those living nearer to composting sites (Aatamila et al 2011;Herr et al 2003a;2003b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are few other studies of health effects in communities living near a composting site (Aatamila et al 2005;Browne et al 2001;Herr et al 2003a;2003b;Kramer et al1989;, and these provide limited evidence of increased exposure levels to bioaerosols at distances greater than 200m to 300m downwind of a composting site (Pearson et al 2015). Three questionnaire-based community health studies reported increases in respiratory symptoms in those living nearer to composting sites (Aatamila et al 2011;Herr et al 2003a;2003b).…”
Section: Discussionmentioning
confidence: 99%
“…There were not enough people living within 250m, where measurements show that concentrations of bioaerosol are most likely to exceed the EA's acceptable levels (Deacon et al, 2009, Pearson et al, 2015, Williams et al, 2013) nor respiratory admissions to reliably investigate respiratory admission risk within the EA 250m precautionary area exclusion zone. Population characteristics were also different from those in other distance bands, with no COAs classified as deprived (Table 2) raising the likelihood of bias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations